2009
DOI: 10.1007/s10549-009-0430-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics of docetaxel-treated human MCF7 breast cancer cells provides evidence of varying cellular responses at high and low doses

Abstract: There is growing evidence that docetaxel, a microtubule-targeting agent like the other taxane paclitaxel, induces dual cytotoxicity mechanism according to dose level. Postgenomics screening technologies are now more and more applied to the elucidation of drug response mechanisms. Proton nuclear magnetic resonance spectroscopy-based pharmacometabolomics was here applied to get further insight into the response of human MCF7 breast carcinoma cells to docetaxel at high (clinical, 5 lM) and low (1 nM) doses. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 48 publications
(74 reference statements)
0
33
1
Order By: Relevance
“…DTX is widely used as a cancer treatment (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the emergence of chemotherapeutic resistance iTHs universal and DTX-resistance responses have been observed in a number of patients (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTX is widely used as a cancer treatment (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the emergence of chemotherapeutic resistance iTHs universal and DTX-resistance responses have been observed in a number of patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel (DTX) is a well-established anti-mitotic chemotherapy agent that functions by interfering with cell division (5). It is used to treat a number of cancer types including metastatic or advanced breast, prostate, thyroid, gastric, ovarian and lung cancer based on its pro-apoptosis potential and its inhibitory effect on angiogenesis and cell viability (6)(7)(8)(9)(10)(11)(12)(13)(14). DTX has also been demonstrated to upregulate growth/differentiation factor 15 and results in chemoresistance in prostate cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Because fatty acid composition was analyzed only in cells surviving docetaxel treatment, this suggests increasing the oleic acid content of the cancer membranes alters its composition and enhances cell survival, as others have also suggested (Baritaki et al, 2007). Docetaxel treatment also increases polyunsaturated fatty acids in MCF7 breast cancer cells (Bayet-Robert et al, 2009), suggesting membrane fluidity as a survival mechanism not unique to T47D cells. Examination of saturation content between phospholipids and lipid droplets also suggests reciprocal lipid content between membrane and storage lipid droplets.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that metabolic change occurs during carcinogenesis [22,23], and it is reported that the metabolic status of tumor cells is associated with proliferation and chemo-sensitivity [24][25][26]. MPCP155 includes some interesting metabolic genes such as ACADSB, SLC27A2 [27], PPARD, BLM, KPNA2 [28], FASN [29][30][31][32], IDH2 [33][34][35], ACSL1 [36], ME1 [37], which are also reported to be associated with carcinogenesis or cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%